Początki kariery naukowej profesora Jana Wasilkowskiego - Dolata, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article concerns the pre-war period in the scientific career of prof. Jan Wasilkowski. This period is associated with the University of Warsaw (from 1935, the Józef Pisudski University), where the scholar worked from the position of an assistant at the Civil Law Seminar (1924), through the habilitation and the degree of associate professor of private law (1929), then deputy professor civil law (1931) and finally associate professor (December 1936). As it turned out, the position of associate professor at the Józef Piłsudski University was not the first choice of the scholar who, in a letter to the Ministry of Religious Affairs and Public Enlightenment, first declared his willingness to be associated with his alma mater (the Jagiellonian University), where he studied and obtained a doctoral degree in 1923. However, by the decision of the Ministry, he took the position of an associate professor at the Józef Piłsudski University and after the war, as a full professor (1947), he reached the highest ranks of the legal world (Dean, Rector, First President of the Supreme Court, Chairman of the Codification Committee). However, the scholar’s pre-war career did not promise that he would become the most influential lawyer of the People’s Republic of Poland, because compared to younger scholars (e.g. Prof. Gwiazdomorski or Prof. Przybyszewski), he achieved the honors of professors and the corresponding reverences somewhat later.
Keywords: Professor Jan Wasilkowski; civil law; professors of the Faculty of Law at the University of Warsaw